Appropriate Testing of Isothiazolinones in Children. Issue 2 (23rd January 2017) - Goldenberg, Alina; Lipp, Michael; Jacob, Sharon E.
Abstract: Background/Objective: The isothiazolinones methylchloroisothiazolinone (MCI) and methylisothiazolinone (MI) are prevalent pediatric contact sensitizers. MI allergic contact dermatitis (ACD) is underreported in the literature. The objective of the current study was to use a database of provider‐reported U.S. pediatric patch test cases to evaluate the positive patch test (PPT) prevalence rates of the combined preservative test substrate MCI/MI and of MI alone. Methods: U.S. pediatric patch test providers in all 50 states who had joined the registry were invited to submit deidentified cases to the database. More than 1100 logged cases in the database were evaluated for PPTs to MCI/MI combination, MCI/MI and MI, and MI alone. Results: Within 1 year of data collection, 96 cases with a PPT for MCI/MI, MCI/MI and MI, and MI alone were identified; 37 of these were positive to MCI/MI, with MI alone not tested or negative, and 39 were positive to MI only, with MCI/MI and MI tested. Fifteen (41%) of the MCI/MI cases were detected using an epicutaneous patch test alone and 22 cases (59%) using comprehensive patch testing. Only one case (3%) of MI alone sensitization was detected using T.R.U.E. plus a supplemental panel of tests; the remaining 38 cases (97%) were detected using comprehensive testing. Testing with only the combined MCI/MI preservative substrate may miss 51% of MI allergies. Conclusion: Appropriate testing of isothiazolinones is needed to clarify the true prevalence of sensitization to these allergens and the burden of pediatric ACD. Patch testing for MI alone in addition to MCI/MI combination is warranted in children with recalcitrant dermatitis.